PERBAIKAN PROSES FERMENTASI BIJI KAKAO KERING DENGAN PENAMBAHAN TETES TEBU, KHAMIR, DAN BAKTERI ASAM ASETAT - Donny Widianto, Ajeng Dara Pramita, dan Sri Wedhastri (Universitas Gadjah Mada, 2013)
Most of cocoa beans produced by smallholder farmers were non fermented which can be improved by modifiedfermentation processing. This study was aimed to inverstigate the influence of molasses, yeast Saccharomycescerevisiae, and Acetobacter aceti addition on dried cocoa beans fermentation process.Fresh cocoa beans were dried in a glasshouse and its reducing sugar was analyzed before and after drying. Asmall plastic bucket (20 cm diameter and 30 cm height) with aeration holes was used as fermentation vessel. Driedcocoa beans were soaked in distilled water for 4 hours, inoculated with yeast and acetic acid bacteria cultures, andmolasses were added at two different concentration, i.e, 1 and 1.5 times of reducing sugar lost during drying.Reducing sugar, ethanol, titrated acid, population of yeast, and acetic acid bacteria were monitored duringfermentation. After fermentation the beans were sun dried and its pH and degree of fermentation were determinedto assess the bean quality.The results showed that the addition of molasses mostly at the level of 1.5, S. cerevisiae, and A. aceti increasereducing sugar, ethanol, titrated acid, yeast and acetic acid bacteria of fermentation liquid (pulp). The highestpercentage of fermented beans (68.4 %) was achieved by addition of S. cerevisiae, A. aceti, and molasses atthe level 1.5. It is likely that the addition of S. cerevisiae, A. aceti, and molasses could improve fermentationprocessing of dried cocoa bean.